Answer to the Soviet Union's Allegation of United States Subversive Activities against USSR and the Other Socialist States - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): William F. Knowland; United States. Mission to the United Nations Refutes all accusations from the USSR that the United States planned the mass uprising of the Hungarian people and that it was a counter-revolution rather than a spontaneous uprising. The truth is that the Hungarian government had to call for help from Soviet army troops, it is strange that it did not call for the Hungarian army, a sizeable military force. It is clear throughout the years of Soviet rule in Hungary, the regime was unable to arm Hungarians to handle an anti-Soviet mobilization in Budapest.